Analisis Hukum Pelaksanaan Perdagangan Derivatif Di Pasar Modal Indonesia - Syazali, Emir Adzan (Bacarita Law Journal, 2024)
The capital market is a main pillar of the modern economy and plays a crucial role in a country's economy. However, trading in the capital market is not free from the risk of crime and violations. One instrument that is increasingly attracting attention in the Indonesian capital market is derivative securities. This study aims to analyze the legal basis governing derivative trading in the Indonesian capital market and identify the benefits and risks associated with trading this instrument. This research uses normative legal research methods with a legislative and comparative approach. Data were collected through literature studies and analyzed descriptively and qualitatively. The results of this study are as follows: The legal basis governing derivative trading in the Indonesian capital market includes Law Number 8 of 1995 concerning the Capital Market, Government Regulation Number 45 of 1995, Government Regulation Number 17 of 2009, and OJK Regulation Number 32/POJK.04/2020. These regulations aim to ensure transparency, security, and market integrity through strict supervision, risk management, and tax compliance. The main benefits of derivative securities include minimizing risk, increasing profits, and securing investments through hedging strategies. However, this instrument also carries high risks and complexities that require deep understanding and good risk management. Derivative trading regulations in the Indonesian capital market provide a comprehensive framework to create a conducive market and attract investment. Derivative securities offer significant profit potential but also bring high risks that require caution and mature strategies in their use.